2021
DOI: 10.5946/ce.2021.071
|View full text |Cite
|
Sign up to set email alerts
|

Acute Gastrointestinal Bleeding in COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: Background/Aims: More than 100 million people to date have been affected by the coronavirus disease-2019 (COVID-19) pandemic. Patients with COVID-19 have a higher risk of bleeding complications. We performed a systematic review and metaanalysis to evaluate the outcomes of COVID-19 patients with signs and symptoms of acute gastrointestinal bleeding (GIB). Methods: A systematic literature search was carried out for articles published until until November 11, 2020, in the Embase, MEDLINE, Web of Science, and Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
2
15
0
1
Order By: Relevance
“…Few studies also looked at the effect of GI bleeding on the outcomes in this specific population such as length of hospital stay, complications, mortality, etc. The consensus from these studies has not shown any impact of GI bleeding on the overall outcomes [ 7 , 12 - 13 ]. Our study showed similar results, as there was no difference in the clinical outcomes between the GI bleed and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies also looked at the effect of GI bleeding on the outcomes in this specific population such as length of hospital stay, complications, mortality, etc. The consensus from these studies has not shown any impact of GI bleeding on the overall outcomes [ 7 , 12 - 13 ]. Our study showed similar results, as there was no difference in the clinical outcomes between the GI bleed and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…First, in the pre-vaccination era, there was a high amount of anxiety among healthcare professionals in the management of these patients due to the high risk of transmission, high mortality, and lack of personal protective equipment early in the pandemic [ 14 , 15 ]. Secondly, early data on COVID-19 patients with GI bleeding showed promising results with conservative management [ 10 - 12 , 16 , 17 ]. In a study including 24 COVID-19 patients with GI bleeding, conservative management alone without any endoscopic intervention was successful in controlling bleeding in all the patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published systematic review and meta-analysis, we revealed that 59% of the COVID-19 patients with AGIB were managed conservatively and less than one-third (31.5%) underwent endoscopic evaluation. Although pooled overall mortality was high 19.1%, pooled mortality directly secondary to AGIB was 3.5% and pooled risk of rebleeding was 11.3% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 ) as well as GI bleeding, including hematochezia and melena [ 16 , 30 , 31 ]. Upper GI bleeding, defined as arising proximal to the ligament of Treitz, is more common than lower GI bleeding and has been reported to respond to conservative management in most of the patients (∼60%) [ 32 , 33 ]. The presence of active GI bleeding in COVID-19 patients and localization of the anatomic source may be diagnosed by radiologists using multiphase CT angiography for active GI bleeding and CT enterography for occult or suspected small bowel bleeding [ 34 ].…”
Section: Discussionmentioning
confidence: 99%